Spontaneous regression of pseudomelanoma - Mastrandrea, V; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
The term pseudomelanoma defines the reappearance of melanic pigmentation on the site of removal of a previous nevus, usally of dermal type. Pseudomelanoma is frequent especially in case of removal of a congenital nevus, both in case of surgical removal or, more frequently, in case of maneuvers such as "curettage" or dermabrasion (1). From a pathogenetic point of view, pseudomelanoma likely arises from going upwards again of melanocytes of the hair follicles, which colonize again the epidermis. This hypothesis is supported by the speckled shape of pseudomelanoma, the latency period of several weeks or months and the repigmentation of vitiligo and halo nevus (2, 3). Nevi and melanoma can really regress also without the halo phenomenon (1). However, a spontaneous regression of pseudomelanoma arisen after surgical removal of a congenital melanocytic nevus has been never reported until now. This report encourages curettage of congenital nevi, the esthetical result of which is negatively affected by the usual appearance of multiple pseudomelanomas.